Recht in der Kirche des Evangeliums - Honecker, Martin (Jus ecclesiasticum, 2008)
Martin Honecker deals with the debate on fundamental principles in Protestant ecclesiastical law, with the question of the theological prerequisites of ecclesiastical law and with the necessary differentiations, such as for example between the law pertaining to the established churches and the law of organization within the church.